Elaboración de una mezcla asfáltica utilizando cenizas residuales de las piladoras y su efecto en las propiedades mecánicas-volumétricas - Cortez Silva, Kelly Anabel (2024)
The present experimental research aims to analyze the volumetric-mechanical factors associated with a modified asphalt mixture as a new alternative for road infrastructure. Rice husk, a large-scale residue from the incineration process in rice mills in the country, was used. The study is based on a quantitative methodology, taking into account the MOP and INEN standards for laboratory testing. Thirty briquettes were produced, varying the percentages based on the filler/bitumen ratio using a formula established by a local road construction company. Different dosages of ash, such as 2%, 4%, 6%, 8%, 10%, and 12%, were added to find the optimal modified dosage. The best results in volumetric-mechanical properties were observed in the 6% ash-modified mixture, showing higher stability and lower flow. It is concluded that using rice husk ash as a replacement for filler improves Marshall parameters and achieves a void percentage within the regulatory range.